1978
DOI: 10.1210/jcem-47-1-151
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Modulation of Calcitonin and Parathyroid Hormone in Man*

Abstract: Recent evidence suggests that of calcitonin (CT) and parathyroid hormone (PTH) is controlled by factors other than the ambient serum calcium concentration. We studied the effects of infusions of four neuroendocrine modulators upon CT and PTH levels: isoproterenol (beta-adrenergic agonist), methoxamine (alpha adrenergic agonist), prostaglandin E2, and somatostatin. Isoproterenol was a consistent secretagogue for both hormones. Maximal CT increments during isoproterenol infusion in normal subjects were 13 +/- 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
3

Year Published

1979
1979
2000
2000

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 27 publications
4
25
3
Order By: Relevance
“…With the clear-cut inhibitory actions of somatostatin ced SLI re-in other tissues in mind, it was obvious to speculate during each that somatostatin present in the thyroid could also [ (20,22,25), whereas some have not been able to disclose any such action (18,21,23,24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the clear-cut inhibitory actions of somatostatin ced SLI re-in other tissues in mind, it was obvious to speculate during each that somatostatin present in the thyroid could also [ (20,22,25), whereas some have not been able to disclose any such action (18,21,23,24).…”
Section: Resultsmentioning
confidence: 99%
“…Thyroid perfusion was performed in mongrel dogs weighing [18][19][20][21][22][23][24][25][26] kg. In the dog, the two thyroid lobes are separate and can be perfused simultaneously and independently.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Lever et al were unable to confirm this, reporting the incidence of coexisting hyperparathyroidism to be only 0.43% [21]. It has been suggested that persistent stimulation of thyroid hormone on adrenergic receptors may lead to hyperparathyroidism [22], which is probably mediated by the induction of f3-adrenergic receptors on parathyroid cells by thyroid hormone [23][24][25]. Along with this hypothesis, Barsotti et al have reported two patients whose PTH levels returned to normal when they became euthyroid [26].…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be due either to unspecific actions or to a direct inhibition of the active calcium transport across the intestinal barrier (Holdsworth, 1975), the latter being mainly regulated by the active metabolites of vitamin D derived from the sequential hydroxylation of vitamin D, by the liver (Blunt, De Luca and Schnoes, 1968) and the kidney (Norman, 1974). Renal hydroxylation which results in the production of the 1,25 (OH) 2 vitamin D 3 is also controlled by calcium (Bikle and Rasmussen, 1975), phosphorus (Gray et at., 1977) and PTH (De Luca, 1978 (Metz et al, 1978). It …”
mentioning
confidence: 98%